Effects of Omega-3 Fatty Acid Supplementation on Diabetic Nephropathy Progression in Patients with Diabetes and Hypertriglyceridemia - Han, Eugene; Yun, Yujung; Kim, Gyuri; Lee, Yong-ho; Wang, Hye Jin; Lee, Byung-Wan; Cha, Bong Soo; Kim, Beom Seok; Kang, Eun Seok (PLOS ONE, 2016)
Beneficial effects of omega-3 fatty acid (O3FA) supplementation in a wide range of disease condition have been well studied. However, there is limited information regarding the effects of O3FAs on chronic kidney disease (CKD), especially in diabetic nephropathy (DN) with hypertriglyceridemia. We investigate whether O3FA supplementation could help maintain renal function in patients with diabetes and hypertriglyceridemia. Total 344 type 2 diabetic patients with a history of O3FA supplementation for managing hypertriglyceridemia were included. Reduction in urine albumin to creatinine ratio (ACR) and glomerular filtrate rate (GFR) were examined. Subgroup analyses were stratified according to the daily O3FA doses. Serum total cholesterol, triglyceride, and urine ACR significantly reduced after O3FA supplementation. Overall, 172 (50.0%) patients did not experience renal function loss, and 125 (36.3%) patients had a GFR with a positive slope. The patients treated with O3FAs at 4g/day showed greater maintenance in renal function than those treated with lower dosages (p < 0.001). This dose dependent effect remains significant after adjustment for multiple variables. O3FA supplementation in diabetic patients with hypertriglyceridemia shows benefits of reducing albuminuria and maintaining renal function. The effects are dependent on the dose of daily O3FA supplementation.